Compression tests on stocky and slender columns of high strength S690 cold-formed square tubes. (15th December 2022) - Xiao, M.; Hu, Y.F.; Shen, M.H.; Chung, K.F.; Nethercot, D.A.
Graphical abstract: Highlights: Fabrication effects of S690 cold-formed square tubes (CFST) were examined. Eight stocky columns of these S690 CFST were tested under compression. Twenty-four slender columns of these S690 CFST were tested under compression. Structural behaviour and deformed modes of all these S690 CFST were evaluated. Improvements to design rules of EN 1993-1 for these S690 CFST were identified. Abstract: An experimental investigation into the structural behaviour of both stocky and slender columns of high strength S690 cold-formed square tubes (CFST) under compression is presented in this paper. A total of 8 stocky columns with two section types of four different cross-sectional dimensions were tested. Moreover, a total of 24 slender columns with two section types of six different cross-sectional dimensions were tested. Typical residual stresses of these two section types were also obtained. As expected, all of these columns of S690 CFST failed under compression similar to those stocky and slender columns of S355 CFST, namely, i) local plate buckling in stocky columns, and ii) overall axial buckling in slender columns. Hence, these tests may be regarded to be confirmatory tests to provide experimental evidence and test data on cross-section resistances of the stocky columns, and member resistances of the slender columns of these S690 CFST. In addition, the measured resistances of these columns were directly compared with those design resistances determined according to Structural Eurocode EN 1993-1-1 based on measured geometrical dimensions and mechanical properties. It is demonstrated that the measured resistances of these columns are significantly larger than those design values, and hence, these test data provide a scientific basis to enhance structural efficiency of the design rules.